2008
DOI: 10.1038/sj.jid.5701153
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between SPINK5 Gene Mutations and Clinical Manifestations in Netherton Syndrome Patients

Abstract: Netherton syndrome (NS) is a congenital ichthyosiform dermatosis caused by serine protease inhibitor Kazal-type 5 (SPINK5) mutations. Tissue kallikreins (KLKs) and lymphoepithelial Kazal-type-related inhibitor (LEKTI) (SPINK5 product) may contribute to the balance of serine proteases/inhibitors in skin and influence skin barrier function and desquamation. SPINK5 mutations, causing NS, lead to truncated LEKTI; each NS patient possesses LEKTI of a different length, depending on the location of mutations. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 41 publications
1
82
0
Order By: Relevance
“…5 Genotype-phenotype correlation in NS is largely incomplete; however, a correlation between the SPINK5 mutation position, LEKTI domain deficiency and disease severity has been suggested. 8,11,12 In our patient, translation of the aberrant transcript deleted of exon 11 is predicted to result in a truncated protein lacking inhibitory domains 5-15. This, combined with the effect of the c.153delT mutation, would be expected to result in a more severe NS phenotype than the one we actually observed in our patient.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 79%
See 1 more Smart Citation
“…5 Genotype-phenotype correlation in NS is largely incomplete; however, a correlation between the SPINK5 mutation position, LEKTI domain deficiency and disease severity has been suggested. 8,11,12 In our patient, translation of the aberrant transcript deleted of exon 11 is predicted to result in a truncated protein lacking inhibitory domains 5-15. This, combined with the effect of the c.153delT mutation, would be expected to result in a more severe NS phenotype than the one we actually observed in our patient.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 79%
“…5,6 The SPINK5 mutation database in NS comprises 62 different mutations, [7][8][9][10] and the genotype-phenotype correlation suggests that downstream mutations may partly allow for residual expression of functional LEKTI fragments, which results in less severe phenotypes. 11,12 Here we report on functional characterization of the c.891C4T variant identified in the SPINK5 gene in an Italian patient with NS. We use patient keratinocytes, minigene constructs and bioinformatic predictors to demonstrate that this synonymous change (p.Cys 297Cys), despite being distant from the acceptor splice site, induces an incomplete exon skipping by affecting a mechanism underlying splicing regulation.…”
Section: Introductionmentioning
confidence: 95%
“…Because NS patients with mutations in exons 1-25 of SPINK5, which encode D1-D12 region of LEKTI, present severe phenotypes, mutations at N-terminal and C-terminal regions in SPINK5 may cause severer and milder phenotypes, respectively (8,9). Because p.Arg578X located in D9 region was reported to cause moderate to severe phenotype (6,8), synonymous mutation, c.474G>A, was considered to be responsible for the milder phenotype in our patient.…”
Section: Discussionmentioning
confidence: 92%
“…Because p.Arg578X located in D9 region was reported to cause moderate to severe phenotype (6,8), synonymous mutation, c.474G>A, was considered to be responsible for the milder phenotype in our patient. Our RT-PCR for c.474G>A detected three transcripts, including two out-of-frame transcripts and an in-frame transcript.…”
Section: Discussionmentioning
confidence: 99%
“…22 We showed that both fragments inhibited rhK5 similarly and established that LEKTI, at least in fragment form, is a potent inhibitor of rhK5 and that this protease may be a target of LEKTI, a physiological inhibitor of multiple serine proteinases, blocks migration and invasion of head and neck squamous cell carcinoma (HNSCC) cells Volume 1 Issue 3 -2014 Arumugam Jayakumar, 1,2 Chandrani Chattopadhyay, 1 Hua-Kang Wu, 1 Katrina Briggs, 1 Ying Henderson, 1 Yaan Kang, LEKTI in human skin. In our later studies we discovered that KLK5, KLK6, KLK13 and KLK14 were potently inhibited by rLEKTI (1)(2)(3)(4)(5)(6), rLEKTI (6-9') and rLEKTI (9)(10)(11)(12). 23,24 We also assessed the basis for phenotypic variations in patients with "mild", "moderate" and "severe" NS.…”
Section: Introductionmentioning
confidence: 99%